2017
DOI: 10.2135/cropsci2016.12.0988
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping of Agronomic and Yield Traits in Two Grain Sorghum Biparental Families

Abstract: The animal industry is a major sector of agriculture in the southeastern United States, but a large deficit exists in regional feed grains needed to support the industry. An increase in production of sorghum [Sorghum bicolor (L.) Moench], a water‐ and nutrient‐use‐efficient cereal, on marginal lands could lead to an alternative crop option for growers and reduce the current grain deficit. Quantitative trait locus (QTL) mapping of grain yield components in two sorghum biparental recombinant inbred line (RIL) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Given the conservation of gene function among closely related cereal species, this presents opportunities for comparative genomics studies to investigate the genetics of grain size in other cereal crops using knowledge gained from gene cloning studies in maize and rice. The sorghum QTL atlas of Mace et al () details around 100 grain weight QTL in sorghum that have been identified through linkage analysis in 18 studies (Bai et al , ; Boyles et al , ; Brown et al , ; Feltus et al , ; Gelli et al , ; Han et al , ; Mocoeur et al , ; Murray et al , ; Paterson et al , ; Phuong et al , ; Rajkumar et al , ; Rami et al , ; Reddy et al , ; Shehzad and Okuno, ; Spagnolli et al , ; Srinivas et al , ; Tao et al , ; Tuinstra et al , ). A further 12 markers associated with grain weight have been identified in three GWAS studies (Boyles et al , ; Upadhyaya et al , ; Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the conservation of gene function among closely related cereal species, this presents opportunities for comparative genomics studies to investigate the genetics of grain size in other cereal crops using knowledge gained from gene cloning studies in maize and rice. The sorghum QTL atlas of Mace et al () details around 100 grain weight QTL in sorghum that have been identified through linkage analysis in 18 studies (Bai et al , ; Boyles et al , ; Brown et al , ; Feltus et al , ; Gelli et al , ; Han et al , ; Mocoeur et al , ; Murray et al , ; Paterson et al , ; Phuong et al , ; Rajkumar et al , ; Rami et al , ; Reddy et al , ; Shehzad and Okuno, ; Spagnolli et al , ; Srinivas et al , ; Tao et al , ; Tuinstra et al , ). A further 12 markers associated with grain weight have been identified in three GWAS studies (Boyles et al , ; Upadhyaya et al , ; Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…As with most crops of value, there are concerns associated with sorghum production, including losses due to abiotic and biotic stress pressure, as well as the desire to enhance composition and increase yield, indicating that a variety of targets exist for trait improvement. Improvement efforts have utilized breeding, coupled with approaches such as QTL identification and mapping, molecular marker identification and genome wide association studies, with the goal of improving germplasm 2 of 18 while also gaining an understanding of the genetic loci/genes/allelic variation contributing to the various traits [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In sorghum breeding, sorghum panicles, the reproductive (flowering) part of a sorghum plant and main yield component, are among the critical components for which phenotypic data are sought [12]. Phenotypic data such as counts, number of seeds per panicle, sizes (panicle length and width) play key roles in various assessments including assessing genetic diversity, selection of new cultivars and estimation of potential yields [13][14][15][16][17][18][19][20]. However, the manual characterization of panicles has proved to a bottleneck to sorghum crop improvement.…”
Section: Introductionmentioning
confidence: 99%